Ovarian Vein Thrombosis as a Complication of Laparoscopic Surgery - Anu Gupta; Natasha Gupta; Josef Blankstein; Richard Trester (Case Reports in Obstetrics and Gynecology)
Ovarian vein thrombosis (OVT) is an extremely rare but life-threatening complication of the postpartum period. It has never been reported as a complication of laparoscopic surgery. We report a case of right ovarian vein thrombosis that occurred in the postoperative period after patient underwent laparoscopic salpingectomy for a right side ectopic pregnancy. She presented with 1-week history of abdominal pain and fever. A complete workup for fever was performed and was found negative. Computed tomography of the abdomen and pelvis revealed right ovarian vein thrombosis. The patient was treated with anticoagulant therapy and responded well.